RANCANG BANGUN ALAT PENDETEKSI DINI OVER HEAT MESIN KENDARAAN MELALUI SUHU AIR PENDINGIN - Alex Surapati; Arif Kurnia; Indra Agustian (Jurnal Teknologi, 2023)
There is currently no cooling system in the vehicle's engine using voice and display instructions that warn the driver that the engine's working temperature has passed a predetermined threshold. To overcome the problems described previously, research was carried out. The result of this research is a tool or device that can detect if there is overheating in the vehicle engine using the DS18B20 sensor. In this tool a warning system is given with voice commands and a display that shows the state of the engine's working temperature at that time. In this study, the Kalman Filter method was used to reduce noise in temperature measurements by the DS18B20 sensor. The results of measuring changes in the average temperature using the Kalman Filter method are 0.019 Â° C and without the Kalman Filter method are 0.58 Â° C. Based on the results of these comparisons using the Kalman Filter method the temperature measurement noise obtained is smaller.